Late Ordovician subsurface carbonates and fossil assemblages from the area immediately west and northwest of Peak Hill in central New South Wales and their regional correlation. Issue 5 (4th July 2022) - Zhen, Y. Y.; Wells, T. J.; Simpson, C. J.; Parslow, J.
Abstract: Late Ordovician conodonts (14 species), corals (five species) and stromatoporoids (two labechiid species) have been recovered from the carbonate intervals intersected in three drill holes in the area located immediately west and northwest of Peak Hill in central New South Wales. The WNDD0001 drill-core section consists of dominantly calcareous and clastic sedimentary rocks in the upper part and andesites in the lower part. The conodont fauna from the carbonate interval at the top confirms an early Katian age ( Taoqupognathus blandus Biozone). The WNDD0002 drill-core section is composed of primarily carbonates in the lower part and dolomitic siltstones and sandstones in the upper part, which have been intruded by andesitic dykes and sills. A distinctive rugose coral species ( Favistina plus ) occurring in the carbonate interval towards the base of the section indicates a middle Katian age ( Taoqupognathus tumidus - Protopanderodus insculptus Biozone). Therefore, the entire WNDD0002 drill-core section is stratigraphically higher than the drill-core section WNDD0001 to form the most complete Upper Ordovician sedimentary succession (unnamed formation) from the northern part of the Junee–Narromine Volcanic Belt. A correlative tabulate coral assemblage of middle Katian age was also recovered from the carbonates in the lower part of the GAMD0001 drill-core section. These new data demonstrate that the Upper Ordovician marine shelf sedimentary facies within these drill holes are comparable with those known from Gunningbland area farther south, a new finding that is important for future geological mapping and mineral exploration in the region. KEY POINTS: For the first time, a Late Ordovician conodont, coral and stromatoporoid fauna is recorded from the northern Junee–Narromine Volcanic Belt in NSW. A wide subsurface distribution of an Upper Ordovician marine shelf succession is confirmed in the region. New biostratigraphic data essential for the future geological mapping and mineral exploration are given for the area.